A New Type of Dehumidifier for Enclosed High-voltage Switchgear Cabinet - Jinbo Zhang; Tongguang Shao; Yu Wang; Jing Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In order to eliminate the internal condensation of enclosed switchgear cabinet, this paper introduced a subminiature and high-performance dehumidifier based on semiconductor refrigeration technology. This equipment utilized a Fuzzy self-tuning PID intelligent controller to monitor the humidity change in the cabinet continuously and judged the dehumidifier start-stop automatically. Besides, real-time communication with a host computer through RS485 interface was also considered. Experiments showed that this design could effectively reduce the internal humidity, eliminate the condensation, and provide a practical and effective solution to prevent the power device accidents caused by wet and condensation. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1555